Connected Vehicle Systems: A Comprehensive Analysis of Technological and Societal Transformations - Utham Kumar Anugula Sethupathy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Connected vehicle systems are revolutionizing transportation through comprehensive integration of vehicle-to-vehicle, vehicle-to-infrastructure, and vehicle-to-pedestrian communications. This technological transformation encompasses multiple domains, from safety and traffic management to urban development and environmental sustainability. These systems enable sophisticated collision prevention, enhance emergency response capabilities, and facilitate dynamic traffic management through real-time data exchange. In urban environments, these technologies are reshaping city development through smart infrastructure integration and optimized resource allocation. Environmental benefits are achieved through eco-driving initiatives, electric vehicle integration, and emissions reduction strategies. The implementation of these systems presents significant social and educational implications, requiring comprehensive public awareness programs and addressing digital divide considerations. Privacy and security frameworks ensure data protection while maintaining system functionality. The advancement of connected vehicle technologies represents a fundamental shift in transportation, requiring careful consideration of technical capabilities, infrastructure requirements, and societal impacts. This comprehensive analysis examines the current state of implementation, challenges, and future directions, highlighting the transformative potential of connected vehicle systems in creating safer, more efficient, and sustainable transportation networks.